The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/toxins15030214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Concentration of Mycotoxins in Animal Feed in the Middle East and North Africa (MENA): A Systematic Review and Meta-Analysis

Abstract: This study seeks a comprehensive meta-analysis of mycotoxin contaminants in animal feed consumed in the Middle East and North Africa (MENA) region. The obtained articles were reviewed, and 49 articles that investigated the contamination of mycotoxins including aflatoxins (AFs), deoxynivalenol (DON), zearalenone (ZEA), T-2 toxin, fumonisins (FUM), and ochratoxin A (OTA), in feed samples or components of animal feed in the MENA region were selected. The titles of the final articles included in the study were met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 136 publications
0
1
0
Order By: Relevance
“…Mycotoxins are posing a serious threat to livestock and consumers due to their toxicity and synergistic characteristics [ 4 ]. Animals ingesting contaminated feeds with a high concentration of mycotoxins showed various effects on their bodies, such as reduced production and suppression of the immune system [ 5 ]. Many outbreaks of mycotoxicosis diseases have been reported in humans and animals due to the consumption of mycotoxin-contaminated food and feed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are posing a serious threat to livestock and consumers due to their toxicity and synergistic characteristics [ 4 ]. Animals ingesting contaminated feeds with a high concentration of mycotoxins showed various effects on their bodies, such as reduced production and suppression of the immune system [ 5 ]. Many outbreaks of mycotoxicosis diseases have been reported in humans and animals due to the consumption of mycotoxin-contaminated food and feed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moldy food, contaminated with FBs (maize, dried figs, grapes, raisins, wine, coffee and some plants), has been found in China, South America, Africa and Europe [14,22,[26][27][28][29][30][31]. Worldwide, human FBs exposure, through moldy maize or animals products, accounts even 354.0 µg/kg body weight per day [32][33][34]. FBs cross the placental barrier and exert many negative effects on fetus development depending on the FBs dose, duration of exposure and time of the exposure [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Zearalenone (ZEN), an estrogenic mycotoxin from Fusarium species that can disrupt cattle reproductive physiology, is one of the most commonly identified mycotoxins in grains and animal feed [ 1 , 2 ]. Several studies reported mycotoxin contamination in feed by detecting the presence of ZEN [ 3 , 4 , 5 , 6 , 7 ]. Despite efforts to minimize mycotoxin concentrations in animal feeds, the prevalence of Fusarium -derived mycotoxins is increasing worldwide.…”
Section: Introductionmentioning
confidence: 99%